Development of a Web-Based Mobile System for the Electronic Archiving of Official Letters in Sumber Rejo Village - Anita, Linda (YHMM PUBLISHING, 2023)
This study aims to develop a web-based mobile system for electronic letter archiving in Sumber Rejo Village, in order to improve the efficiency and transparency of administrative letter management. The main issue faced by the village was manual archiving, which is prone to data loss and time-consuming retrieval. Using the Software Development Life Cycle (SDLC) method, the system was designed with features such as incoming and outgoing letter recording, data search, and cloud-based storage. The results show that the system improves administrative speed, data accuracy, and ease of access to information for both village staff and the public. The implementation of this system also supports the enforcement of Law No. 14 of 2008 on Public Information Disclosure, which guarantees citizens' rights to access information from government institutions. Therefore, the system is expected to be an innovative solution for modernizing village governance towards greater efficiency and transparency.